Taiwan in the Asia-Pacific in the 1990s (St. Leonards, N.S.W. : Allen & Unwin, 1994)
This book is about: Taiwan's domestic political reforms, Institutional change and power realignment; Emerging Taiwanese identify in the 1990s; The Rise of Island-China separatism; ...
Keywords: Asia; Taiwan; Pacific Area; Taiwan -- Foreign economic relations -- Asia -- Congresses; Asia -- Foreign economic relations -- Taiwan -- Congresses; Taiwan -- Foreign economic relations -- Pacific Area -- Congresses; Pacific Area -- Foreign economic relations -- Taiwan -- Congresses